Creative Map Instruction: An Experimental Effect on Biology Students’ Mental Ability (American International Journal of Humanities, Arts and Social Sciences, 2019)
The study investigated the effect of creative map on senior secondary biology students’ mental ability. Three research questions were raised and answered. The research design was a quasi-experimental pretest, posttest control group design. Two randomly selected schools involving a total of 71 biology students participated in the study. Biology Achievement Test (BAT) and Attitude towards Biology Questionnaire (ABQ) served data collection process. The sample were grouped into three ability levels (High, Medium and Low) using BAT before and after treatment administration. The experimental group was taught using creative map package while the control group was exposed to lecture method. Data collected was analyzed using frequency count, mean and Analysis of Variance. The result (F(1,61) =38.44; p